(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the historical and environmental aspects of the rational use and protection of nature and its resources are examined using the example of the Fergana Valley. The significance of “Holly Places” in ensuring their sustainability in nature is also analyzed.